Expressão dos marcadores ki-67, cox-2 e caspase-3 clivada em pele de ratos expostos à radiação ultravioleta e a agrotóxico organofosforado - Fernandes, Tania Rita Moreno de Oliveira [UNIFESP] (2017)
Ultraviolet radiation and pesticides are proven to be carcinogenic to several organs and tissues. We investigated, by immunohistochemical techniques, the Ki-67, Cox-2 and Cleaved Caspase-3 clivada markers as indicators of neoplastic or pre-neoplastic changes in the skin of rats exposed to these two variables in an isolated or associated way. Forty-four Wistar female rats with three months of age, average weight of 200 ± 30g, were used. The animals were divided into four random groups, each one with 10 animals and observed for 15 weeks. Group A was the control group. Group B was exposed to UVR-B. The animals from group C were exposed to UVR-B followed by a layer of pesticide and, in group D, only one layer of pesticide was applied to the skin of the animals. At the end of the 15th week of the experiment, the animals were euthanized and their lesions resected, submitted to histopathological and immunohistochemical examination and analyzed by the hematoxylin-eosin staining and streptavidin-biotin-peroxidase methods. In group D - exposed only to the organophosphorus pesticide, a predominance of atrophy of the skin and its appendages were observed. Control group did not presented changes. At the end of the experiment, in response to UVR-B and UVR-B + pesticide, all the animals had cellular alterations indicative of neoplasia or cutaneous pre-neoplasia. Considering the immunohistochemical analysis, in relation to Ki-67, we observed that it was not possible to evince statistically significant difference among the groups. However, we observed that the group D (pesticide), even without clinical alterations, presented a high percentage of this protein already. Cox-2 was modestly expressed in the UVR-B + pesticide and pesticide groups. Only the animals in the UVR-B group expressed it mostly. Differently than expected, low immunostaining was evidenced when UVR-B was associated with the pesticide. Cleaved caspase-3 clivada presented 100% positivity in all study groups except control group, with no statistical differences among them. We conclude that UVR-B was responsible for most of the alterations found, And that the organophosphorus pesticide showed increased immunohistochemistry of proliferative cutaneous cellular activity through the increase of Ki-67.